An evaluation of the habitable quality of bed spaces in Krus na Ligas - Ty, Maria Katrina Cheradee Bernardo
This study shows the evaluation of the habitable qualities of the bed spaces in Krus na Ligas and the effect of the existing air space and ventilation conditions of the spaces on the thermal comfort of the occupants. The National Building Code is used as a reference for the standards of habitable rooms. As space and ventilation problems are becoming prevalent in bed spaces within the vicinity of the University of the Philippines Diliman these times, it is timely to look into the relationship between the built environment and coping mechanisms of bed spacers. Evaluative method was used in this study applying cluster sampling of the 30 respondents occupying the ten bed spaces which were purposively chosen. Measurement was used in evaluating and was supported by survey questionnaire and observation. Habitable rooms standards set by the Code were utilized to evaluate the data at hand. Comparison of room measurements and Code standards were shown in tables and validity of bed spacers' responses were presented using univariate matrices. The study suggests that although the bed spaces in Krus na Ligas have Code conforming features such as: ceiling height, floor area and window area, the occupancy pattern, which generates crowd, is to be regulated. Overcrowding stimulated the occupants to feel uncomfortable and worn out. They cannot concentrate with their activities inside the bed spaces. This gives them reasons to go out and use cooling devices, specifically electric fans. The usual high frequency usage of electric fans among the bed spacers results to consumption of electricity. The study concludes that the habitable quality of bed space does not depend only on the conformance of the structures to Code requirements. It implies that the number of occupants, together with occupancy pattern, greatly affects the habitable quality of a room.